How the probability of presentation to a primary care clinician correlates with cancer survival rates: a European survey using vignettes - Michael Harris; Peter Frey; Magdalena Esteva; Svjetlana Gašparović Babić; Mercè Marzo-Castillejo; Davorina Petek; Marija Petek Ster; Hans Thulesius (Taylor & Francis Group, 2017)
Objective: European cancer survival rates vary widely. System factors, including whether or not primary care physicians (PCPs) are gatekeepers, may account for some of these differences. This study explores where patients who may have cancer are likely to present for medical care in different European countries, and how probability of presentation to a primary care clinician correlates with cancer survival rates. Design: Seventy-eight PCPs in a range of European countries assessed four vignettes representing patients who might have cancer, and consensus groups agreed how likely those patients were to present to different clinicians in their own countries. These data were compared with national cancer survival rates. Setting: A total of 14 countries. Subjects: Consensus groups of PCPs. Main outcome measures: Probability of initial presentation to a PCP for four clinical vignettes. Results: There was no significant correlation between overall national 1-year relative cancer survival rates and the probability of initial presentation to a PCP (r  = −0.16, 95% CI −0.39 to 0.08). Within that there was large variation depending on the type of cancer, with a significantly poorer lung cancer survival in countries where patients were more likely to initially consult a PCP (lung r = −0.57, 95% CI −0.83 to −0.12; ovary: r = −0.13, 95% CI −0.57 to 0.38; breast r = 0.14, 95% CI −0.36 to 0.58; bowel: r = 0.20, 95% CI −0.31 to 0.62). Conclusions: There were wide variations in the degree of gatekeeping between countries, with no simple binary model as to whether or not a country has a "PCP-as-gatekeeper" system. While there was case-by-case variation, there was no overall evidence of a link between a higher probability of initial consultation with a PCP and poorer cancer survival.KEY POINTS European cancer survival rates vary widely, and health system factors may account for some of these differences. The data from 14 European countries show a wide variation in the probability of initial presentation to a PCP. The degree to which PCPs act as gatekeepers varies considerably from country to country. There is no overall evidence of a link between a higher probability of initial presentation to a PCP and poorer cancer survival.